Below-the-knee Amputation with Targeted Muscle Reinnervation: Operative Technique and Technical Pearls. Issue 3 (27th March 2023) - Chang, Brian L.; Kleiber, Grant M.
Abstract : Background: Postamputation pain from symptomatic neuromas and/or phantom limb pain can have a significant detrimental impact on patients' quality of life following a major lower extremity amputation. Various methods of physiologic nerve stabilization, such as targeted muscle reinnervation (TMR) and regenerative peripheral nerve interface, have been proposed as the best current techniques to prevent that pathologic neuropathic pain. Methods: This article details our institution's technique that has been performed safely and effectively on over 100 patients. Our approach and rationale for each of the major nerves of the lower extremity are presented. Results: In contrast to other described techniques for TMR for below-the-knee amputations, this current protocol does not involve performing transfers on all five major nerves, as one must balance rates of symptomatic neuroma formation and nerve-specific phantom limb pain with needed operative time and surgical morbidity from removing proximal sensory function and denervation of the donor motor nerve branches. This technique also differs significantly from others by performing a transposition of the superficial peroneal nerve to place the neurorrhaphy away from the weight-bearing stump. Conclusion: This article details our institution's approach to physiologic nerve stabilization via TMR at time of below-the-knee amputation.